Aransemen Nada Alto, Tenor, dan Bass Menggunakan Algoritma Genetika - Hendry Setiawan; Windra Swastika; Ossie Leona; Oesman Hendra Kelana (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
Harmony is the key element in producing a piece of music. When a song will be sung by the choir, the song should be arranged in a division of soprano, alto, tenor, and bass voice parts first. Unfortunately, not everyone has the ability to determine the harmonic notes division. There are theories to make a harmonic division of voice parts. Based on the theories, an application for notes arrangement can be developed. The application development uses Application Programming Interface (API) JFugue that can represent music as programming script. Genetic Algorithm is used to implement the application. Chromosome in Genetic Algorithm contains the music notes that have translated into the value of algorithmic music and its duration. Selection is done by giving a reward for the correct notes arrangement and punishment for the wrong notes arrangement. The testing result of this application is already showing a good result. The results of fitness function are in accordance with the verification result from the expert. The average percentage of truth note arrangement is above 98%.